CARACTERIZACIÓN DE CANDIDA SPP. AISLADAS A PARTIR DE UROCULTIVOS EN LA CIUDAD DE MEDELLÍN - Clara M. Duque (Asociación Colombiana de Infectología, 2020)
Candida spp is an important etiologic agent in urinary tract infections, mainly in patients in broad-spectrum antifungal therapy, with urinary catheters. Candida. albicans is the most frequent specie; but other species have arised as emerging pathogens. In this study, isolates of Candida spp. of urine cultures from patients who consulted in Dinamica IPS between January 2016 and November 2017 were evaluated. To estimate the frequency of the species and to observe the sensitivity patterns, the phenotypic identification and its sensitivity profile was performed employed the Vitek 2® commercial system. (BioMérieux, Inc) In addition the isolates were evaluated by sequence analysis and phylogenetics ITS1-5.8S-ITS2. This study included 78 isolates of Candida spp. The frequencies of Candida species identified using the molecular tools were: C. albicans (38.5%), C. tropicalis (23.1%), C. glabrata (21.8%), C. parapsilosis (10.3%), C. guillermondi (1.3%) and C. metapsilosis and C. krusei (2.5%). The identification by molecular methods and by Vitek 2 system were: C. albicans (93.3%), for C. glabrata (94.1%), C. tropicalis (83.3%), C. parapsilosis (75%) and 100% for C. guilliermondii and C. krusei.. fluconazole sensitivity of all isolates was 93.6%